Treatment decision-making among patients with oropharyngeal squamous cell cancer: A qualitative study. (January 2021) - Windon, Melina J.; Le, Daisy; D'Souza, Gypsyamber; Bigelow, Elaine; Pitman, Karen; Boss, Emily; Eisele, David W.; Fakhry, Carole
Highlights: Oropharyngeal cancer patients endorsed distress at diagnosis and decisional conflict. Decisional factors included doctor's recommendation and avoidance of adverse effects. Patients inhabit multiple decisional roles, with varying degrees of autonomy. A desire for patient-centered information was apparent. Our findings can be used to guide patient-centered communication. Abstract: Oropharyngeal squamous cell cancer (OPSCC) is now the most common site of head and neck squamous cell cancer. Despite the focus on treatment deintensification in clinical trials, little is known about the preferences, experiences and needs of patients with OPSCC when deciding between surgery and radiation therapy as primary treatment with curative intent. In this qualitative study, pre-treatment and post-treatment oropharyngeal cancer patients were recruited to take part in one-on-one interviews (n = 11 pre-treatment) and focus group discussions (n = 15 post-treatment) about treatment decision-making. Recordings were transcribed and assessed for emergent themes using framework analysis. From the one-on-one interviews and focus group discussions with OPSCC patients, fourteen themes were identified. Participants expressed alarm at diagnosis, decisional conflict, and a variety of roles in decision-making (physician-controlled, shared, and autonomous). Decisions were driven by the perceived recommendation of the treatment team, a desire for physical (surgical) tumor removal, fear of adverse effects of treatment, and patient-specific values. Although participants felt well-informed by their treating physicians, they identified a need for additional patient-centered information. Participants were critical of the poor quality of information available on the internet, and acknowledged the advantage of hearing the experiences of post-treatment patients. The experiences identified herein may be used to guide patient-centered communication during patient counseling and to inform interventions designed to support patients' needs at diagnosis, ultimately helping to implement high-quality, patient-centered care.